L'UTILISATION DE LA BANDE DESSINEE LES AVENTURES DE TINTIN POUR AMELIORER LA COMPETENCE DE LA COMPREHENSION ECRITE - Rizkitasari, Citra (2015)
This article is to examine the use of "Les Aventures de Tintin" story telling media book as a part of learning how to reading in French at high school easily, and to obtain information about the advantages and benefits of this media. Through the application of this media, it can be useful for motivated and help student reading French language in certain type of themes in the syllabus of French language school. Results of the study showed that "Les Aventures de Tintin" story telling media book can be implemented in learning French language for beginner. Artikel ini bertujuan untuk mengkaji penggunaan media buku cerita bergambar "Les Aventures de Tintin" sebagai bagian dari belajar untuk membaca bahasa Perancis disekolah dengan mudah dan untuk memperoleh informasi mengenai kelebihan dan manfaat penggunaan media ini dalam pembelajaran bahasa Perancis. Melalui penerapan media ini, diharapkan dapat berguna dalam memotivasi dan membantu siswa dalam membaca bahasa Perancis sesuai dengan tema-tema pada silabus bahasa Perancis di SMA. Hasil kajian menunjukKan bahwa media buku cerita bergambar "Les Aventures de Tintin" dapat diimplementasikan dalam pembelajaran bahasa Perancis tingkat pemula.